Automorphism groups of tetravalent Cayley graphs on minimal non-abelian groups - Ghasemi, M. (Algebra and Discrete Mathematics, 2012)
A Cayley graph X = Cay(G, S) is called normal for G if the right regular representation R(G) of G is normal in the full automorphism group Aut(X) of X. In the present paper it is proved that all connected tetravalent Cayley graphs on a minimal non-abelian group G are normal when (|G|,2) = (|G|,3) = 1, and X is not isomorphic to either Cay(G, S), where |G| = 5n, and |Aut(X)| = 2m.3.5n, where m ∈ {2,3} and n ≥ 3, or Cay(G, S) where |G| = 5qn (q is prime) and |Aut(X)| = 2m.3.5.qn, where q ≥ 7, m ∈ {2,3} and n ≥ 1.